Analysis Of The Differences In Running Intervals On Running Speed Of Students At Mts Al Amin Pakis - Arifin Arifin; Wiwik Kusmawati (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to determine the difference in running intervals on running speed in MTs Al Amin Pakis students. The research method is a quasi-experimental method. The sampling technique is simple random sampling. The sample is 20 students of class VIII A as the experimental class and 20 students of class VIII B as the control class. The data collection technique uses tests and non-tests. The instruments are tests and non-test instruments in the form of questionnaires. The data obtained were analyzed using prerequisite tests for normality tests and homogeneity tests. The results of the t-test that have been carried out with the SPSS program, obtained that the t-count value is greater than the t-table value, meaning that there is a significant difference in running intervals on running speed in MTs Al Amin Pakis student.